Electrochemical Behaviour of Titanium Alloys And Stainless Steel In Different Simulated Body Fluid - Rozlin binti Nik Mohd Masdek, Nik; Salleh, Zuraidah; Abidin Kamarul, Zainal; Zin Abu, Md (International Journal of Engineering and Technology, 2018)
Biomaterials, such as titanium and 316L stainless steel, are widely used as an implant material for many health problems such as cardio stents, orthopedic and dental implant. The main concern about these biomaterials is corrosion. The biomaterials can easily corrode when exposed in human body fluid. The objective of the study is to compare the corrosion rate of titanium and 316L stainless steel in three different simulated body fluid solutions (SBF). Three different SBF that being used are Phosphate Buffered Saline (PBS) Solution, Hankâ€™s Solution and Ringer Solution. The SBF will act as an electrolyte in the three-electrochemical cell. The Gamry potentiostat machine was used to run the Open Circuit Potential (OCP) and Potentiodynamic Polarization (PDP) to obtain the corrosion rate of the samples. The phase identification and microstructure of the samples were studied using the XRD and optical microscope, respectively. Based on the results obtained it can be concluded that even though 316L SS has shown a very good corrosion resistant, however titanium is more viable option as a bioimplant material in terms of its durability and efficiency.Â Â